Cervical cancer awareness and knowledge gaps among female high school teachers in Benghazi, Libya - Hussien Hamid; Nour E. Almansoury; Zobyda I. Elreshi; Mohamed H.S. Ahmida; Abdulla M. Elmansoury; Mohamed Najah (Scientific African)
Objective: This study assessed awareness of cervical cancer warning signs, symptoms, and risk factors among female high school teachers in Benghazi, Libya, and examined sociodemographic associations with knowledge gaps. Methods: This cross-sectional study targeted a population of 3892 female high school teachers in Benghazi, Libya. Based on a 95 % confidence interval and a 5 % margin of error, a minimum sample size of 350 participants was calculated using the Qualtrics.com sample size calculator. Ultimately, 200 teachers participated, resulting in a response rate of 57.1 %. Data were collected through face-to-face interviews utilizing the validated Cervical Cancer Awareness Measure (Cervical CAM) toolkit, which assessed awareness via both prompted and unprompted recall. Associations between awareness levels and sociodemographic variables (such as age and educational qualification) were analyzed using chi-square tests and ordinal logistic regression in SPSS v25.0, with statistical significance set at p < 0.05. Results: Unprompted recall revealed that 60.5 % of participants could not identify any cervical cancer symptoms, while the rest identified only two—intermenstrual bleeding and malodorous discharge (18.2 %). Awareness improved with prompting, with vaginal bleeding being the most recognized symptom (78.5 % intermenstrual, 74 % postmenopausal), while nonspecific symptoms (e.g., pelvic pain [47 %], blood in stool/urine [30 %]) remained poorly identified. Composite scores indicated that 57.5 % had good symptom awareness; however, only 5 % felt ‘very confident’ in recognizing symptoms. Strikingly, no participant independently recalled risk factors. After prompting, 75.5 % remained unaware of HPV’s role, and 69 % did not recognize the importance of Pap tests. Symptoms awareness was significantly associated with higher education (Cramer’s V = 0.28, p = 0.001) and number of children (Cramer’s V = 0.22, p = 0.013), but no significant associations were found between sociodemographic factors and risk factor awareness. Conclusions: Female high school teachers in Benghazi exhibit limited awareness of cervical cancer symptoms and key risk factors, highlighting the need for school-based educational programs and targeted media campaigns to address these knowledge gaps.